2003
DOI: 10.1093/ndt/18.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping is a potent predictor of cardiovascular mortality and is associated with autonomic dysfunction in haemodialysis patients

Abstract: The non-dipping phenomenon is closely related to a high incidence of CV diseases, a poor long-term survival and profound autonomic dysfunction. ABPM is useful in predicting long-term CV prognosis in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
136
2
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(156 citation statements)
references
References 19 publications
7
136
2
11
Order By: Relevance
“…It is well known, indeed, that patients with PA loose blood pressure circadian rhythm and become non-dipper, a condition associated with an increased risk for cardiovascular events (36,37). In our patients, 24 h blood pressure monitoring showed that after surgery patients with small adenoma restored blood pressure circadian rhythm at variance with patients with a bigger adenoma.…”
Section: Discussionsupporting
confidence: 50%
“…It is well known, indeed, that patients with PA loose blood pressure circadian rhythm and become non-dipper, a condition associated with an increased risk for cardiovascular events (36,37). In our patients, 24 h blood pressure monitoring showed that after surgery patients with small adenoma restored blood pressure circadian rhythm at variance with patients with a bigger adenoma.…”
Section: Discussionsupporting
confidence: 50%
“…22 Another prospective study found higher rates of cardiovascular mortality and coronary artery stenosis in ND patients compared to D patients undergoing HD. 23 Based on these studies and our results, we suggest that a deteriorated diurnal blood pressure rhythm parallels the malnutrition status in patients undergoing HD. Interestingly, which is an indicator of hypervolemia, cardiothoracic index of the patients with ND and RD pattern was significantly higher than patients with D pattern.…”
Section: Discussionsupporting
confidence: 71%
“…Related studies have revealed that nighttime blood pressure is associated with LVH [18][19][20][21] and is a predictor of negative cardiovascular outcomes in patients undergoing HD. 22,23 One study reported that cardiovascular survival was worse in patients with the ND blood pressure pattern compared to patients with the D blood pressure pattern, and it stated that an elevated 24 h pulse pressure and nighttime systolic blood pressure were associated with cardiovascular mortality. 22 Another prospective study found higher rates of cardiovascular mortality and coronary artery stenosis in ND patients compared to D patients undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with secondary hypertension (2), autonomic failure (3), and chronic renal failure (CRF) (4) are particularly prone to loss of circadian BP rhythmicity, which also relates to their cardiovascular prognosis (5). In patients with CRF, derangements of diurnal BP rhythmicity have been associated with the degree of renal dysfunction (6), the rate of progression of renal failure (7), and with changes in the autonomic nervous system (5,8).…”
mentioning
confidence: 99%